2018
DOI: 10.1021/acssuschemeng.7b04373
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Application of Acid Leaching to Regenerate Li(Ni1/3Co1/3Mn1/3)O2 Cathodes from Spent Lithium-Ion Batteries

Abstract: Rapid development of energy storage system causes a burst demand of lithium-ion batteries (LIBs), and large number of spent LIBs with high valuable metals are produced. Here we propose a novel application of oxalic acid leaching to regenerate Li(Ni 1/3 Co 1/3 Mn 1/3 )O 2 (NCM) cathodes from spent LIBs. With lithium dissolving into the solution, the transition metals transform into oxalate precipitates and deposit on the surface of spent NCM cathodes, separating lithium and transition metals in one simple step.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(101 citation statements)
references
References 37 publications
1
79
0
1
Order By: Relevance
“…Oxalate has also been demonstrated as an effective coprecipitation agent to achieve a similar effect . Along these lines, Zhang et al demonstrated a unique proof‐of‐concept approach where pure NMC powder was leached with oxalic acid. As mentioned previously, oxalic acid generates MC 2 O 4 (M = Ni, Co, and Mn) precipitate, and thus Li + was selectively leached, while the powder suspension comprised MC 2 O 4 and unreacted NMC.…”
Section: Cathode Resynthesis Directly From Leachatementioning
confidence: 99%
“…Oxalate has also been demonstrated as an effective coprecipitation agent to achieve a similar effect . Along these lines, Zhang et al demonstrated a unique proof‐of‐concept approach where pure NMC powder was leached with oxalic acid. As mentioned previously, oxalic acid generates MC 2 O 4 (M = Ni, Co, and Mn) precipitate, and thus Li + was selectively leached, while the powder suspension comprised MC 2 O 4 and unreacted NMC.…”
Section: Cathode Resynthesis Directly From Leachatementioning
confidence: 99%
“…Yao et al [74] used similar strategy to attain good electrochemical performance with the regenerated cathode, NCM. [78] In addition to the organic acids leaching, usage of conventional inorganic acids has also been investigated. The same group found that regenerated NCM via sol-gel process could be able to achieve 139 mAh g −1 after 30 cycles.…”
Section: Resynthesis Of Ncmmentioning
confidence: 99%
“…Recently, merely 0.6 m oxalic acid is applied to recover the maximum amount of metal ions in a short time without the assistance of dangerous H 2 O 2 . It can be seen that the regenerated product from 10 min delivered the discharge capacity of 154 mAh g −1 after 150 cycles inspiring the battery research to design cathode material from spent LIBs …”
Section: Spent Materials In Libsmentioning
confidence: 99%
“…A review of the available literature supports the efficacy of hydrometallurgical processing over the pyro and bio metallurgical recycling strategies [18][19][20][21]. The hydrometallurgical processes usually consist of a leaching step for solubilizing the metals into either mineral acid solutions (HCl, H 2 SO 4 , H 3 [22][23][24][25][26][27][28][29][30][31][32]. Pregnant leach liquor is treated by various separation and purification steps to recover the metal values [18,21].…”
Section: Introductionmentioning
confidence: 99%